Underprivileged Voters and Electoral Exclusion in Contemporary Europe - Tuorto, Dario (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Inequality in people's vote participation boosts the challenges to democracy originating from trends of falling turnout. Tuorto's engaging book offers a thoroughly theoretical and empirical exploration of the causes and consequences of falling turnout among unprivileged segments of society, whose abandonment of the polling booth has widened with the inception of the Great Recession. A must-read for the political behaviour community and for all concerned about the prospects of representative democracy." - Professor Paolo Bellucci, University of Siena, Italy This volume investigates the reasons behind contemporary participatory inequality, the form and dimensions it assumes in relation to the institutional constraints that regulate access to the electoral arena and socio-cultural transformations which have altered both the class structures and the territorial basis of voting. At the same time, it analyses the effects that the intensification of these processes risk to produce, if uncontrolled, on the stability of the democratic system and on the individual life of voters, deprived of institutional representation and left with the alternatives of protest (channelled by existing parties or elements outside the party system) or detachment from politics. Dario Tuorto is Associate Professor in Sociology at the Department of Education, University of Bologna, Italy.
Chapter 1. Introduction -- Chapter 2. Voter turnout and imperfect inclusivity: a democratic problem -- Chapter 3. Turnout and socio-economic inequality at the individual level -- Chapter 4. The institutional determinants of turnout inequalities -- Chapter 5. Voting in times of crisis. From opting out to regaining a voice.
Keywords: Europe-Politics and government; Elections; Political sociology; European Politics; Electoral Politics; Political Sociology